Study protocol for a 9-month randomised controlled trial assessing the effects of almonds versus carbohydrate-rich snack foods on weight loss and weight maintenance. Issue 7 (19th July 2020) - Carter, Sharayah; Hill, Alison M; Yandell, Catherine; Buckley, Jonathan D; Tan, Sze-Yen; Rogers, Geraint B; Childs, Jessie; Matheson, Mark; Lamb, Kate; Ward, Susan; Stanton, Tasha R; Fraysse, Francois; et al.
Abstract : Introduction: Epidemiological studies indicate an inverse association between nut consumption and body mass index (BMI). However, clinical trials evaluating the effects of nut consumption compared with a nut-free diet on adiposity have reported mixed findings with some studies reporting greater weight loss and others reporting no weight change. This paper describes the rationale and detailed protocol for a randomised controlled trial assessing whether the inclusion of almonds or carbohydrate-rich snacks in an otherwise nut-free energy-restricted diet will promote weight loss during 3 months of energy restriction and limit weight regain during 6 months of weight maintenance. Methods and analysis: One hundred and thirty-four adults aged 25–65 years with a BMI of 27.5–34.9 kg/m 2 will be recruited and randomly allocated to either the almond-enriched diet (AED) (15% energy from almonds) or a nut-free control diet (NFD) (15% energy from carbohydrate-rich snack foods). Study snack foods will be provided. Weight loss will be achieved through a 30% energy restriction over 3 months, and weight maintenance will be encouraged for 6 months by increasing overall energy intake by 120–180 kcal/day ( 500-750kJ/day) as required. Food will be self-selected, based on recommendations from the study dietitian. Body composition, resting energy expenditure, total daily energy expenditure (via doubly labelled water), physical activity, appetite regulation, cardiometabolic health, gut microbiome, liver health, inflammatory factors, eating behaviours, mood and personality, functional mobility and pain, quality of life and sleep patterns will be measured throughout the 9-month trial. The effects of intervention on the outcome measures over time will be analysed using random effects mixed models, with treatment (AED or NFD) and time (baseline, 3 months and 9 months) being the between and within factors, respectively in the analysis. Ethics and dissemination: Ethics approval was obtained from the University of South Australia Human Research Ethics Committee (201436). Results from this trial will be disseminated through publication in peer-reviewed journals, national and international presentations. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12618001861246).